The Nuance of Divine Romanticism in Religious Discourse: A Transitivity Approach to the Al-Qur’an Translation in Local Languages - Suparno, Darsita; Amsariah, Siti; Zakaria, Muhammad Fadhlurrahman (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study aims to examine God’s romantic communication with His servants in the translation of the Qur’an into Palembang and Osing Javanese using Systemic Functional Linguistics. This research highlights the ideational function (representation of divine love), interpersonal function (the God-servant relationship in language), and textual function (cohesion and coherence in constructing divine romanticism). This study employs a qualitative method based on the transitivity system in SFL, analyzing material, mental and relational processes in both translations. The finding reveal that the Palembang translation predominantly employs mental and relational processes, portraying God as a compassionate and paternalistic figure. Meanwhile, the Osing Javanese translation emphasizes material and existential processes, constructing a more expressive romantic relationship. From an interpersonal perspective, modality and mood system analysis demonstrates that both translations construct a close God-servant relationship, albeit with different expressions of divine love. This study contributes to SFL-based translation studies in religious discourse and enriches the understanding of ecotheology, particularly in divine love, human harmony, and religious values are expresses through linguistics structure in divine communication. The findings serve as reference for the development of more communicative and contextually relevant Qur’anic translations, while also fostering awareness of spiritual and ecological interconnectedness.